Rainwater harvesting for groundwater recharge: A case study on sustainability of watershed development initiative in Aravali hills of Rajasthan - GREWAL, S. S. (Journal of Soil and Water Conservation, 2020)
Groundwater meets multiple needs of the society but is depleting at a fast rate because of over exploitation particularly in arid and semi-arid ecosystems of India. Watershed development is reported to augment groundwater supply but agricultural development that follows often leads to more extraction causing sustainability concerns. The fact remains that rainwater harvesting has to be scaled up to augment the groundwater supply to the extent possible so that food security risks are kept at bay. This paper reports the results of a corporate supported project on rainwater harvesting for groundwater recharge by the construction of series of earthen dams and in situ rainwater conservation by levelling and terracing the wastelands. A case study of one typical village out of 35 covered in Aravali foot Hills of Alwar district of Rajasthan was taken for detailed analysis. Total investment made from the year 2008 to 2014 was Rs. 41.75 lakh out of which 67.08% was spent on land levelling and field bunds, 18.41% on 16 earthen dams and gully plug, 7.60% on plantation, 5.87% on village development activities and 1.03% on crop demonstrations. Two dams were selected for monitoring rainwater harvesting by installing gauges and result extrapolated for 16 dams. The five years (2010 to 2014) mean annual rainfall was 578 mm with high variability from low of 269 and high of 1172 mm and monsoon rainfall was 86.50% of total rainfall. The household survey revealed that between 1975 and 2014, the number of tube wells increased from 1 to 106 and the average ground water table went down from 9.6 to 18.3m in this period. Forty four tube-wells were added in 7 project years and 46 percent tube wells were converted from diesel pumps to electricity driven submersible motors. The rate of ground water depletion was inversely proportional to rate of increase in the number of bore wells. There was a clear downward spiral after 1995-2000 when land development activity triggered the jump in tube well installation. The yearly fluctuation in water table was, however, influenced by rainfall amount and distribution. The record of water levels in three typical wells indicated general drop in the ground water level from 0.66 to 1.50 meter in six years. More land reclamation was leading to more ground water exploitation in spite of installation of sprinkler irrigation. The wasteland and undulated lands were converted to cultivated productive land by means of land leveling and field bunding over an area of 102.91 ha from 2009 to 2014 at a cost of Rs. 71.90Lakh out of which farmers contributed 61.05 percent and project share was 38.95 percent. The post project household survey conducted in 2015-16 indicated increase in crop production, green and dry fodder availability and milk production. A major part of increased income was reinvested in farm development and installation of irrigation system. Though production gains and net benefits through rainwater harvesting and land development improved livelihood opportunities but this gain was at the cost of over exploitation of ground water leading to lowering of water table. The demand management by selection of drought resistant crops, efficient sowing methods, short rotation varieties and most judicious use of water appears only possible way out.